Toll-Like Receptor Ligand-Based Vaccine Adjuvants Require Intact MyD88 Signaling in Antigen-Presenting Cells for Germinal Center Formation and Antibody Production - Mosaheb, Munir M.; Reiser, Michael L.; Wetzler, Lee M. (Frontiers in Immunology, 2017)
Vaccines are critical in the fight against infectious diseases and immune stimulating adjuvants are essential for enhancing vaccine efficacy. However the precise mechanisms of action of most adjuvants are unknown. There is an urgent need for customized and adjuvant formulated vaccines against immune evading pathogens that remain a risk today. Understanding the specific role of various cell types in adjuvant-induced protective immune responses is vital for an effective vaccine design. We have investigated the role of cell specific MyD88 signaling in vaccine adjuvant activity in vivo, using Neisserial PorB, a TLR2-ligand based adjuvant, compared with an endosomal TLR9 ligand (CpG) and TLR-independent (Alum, MF59) adjuvants. We found that intact MyD88 signaling is essential, separately, in all three APC types (B cells, macrophages and DCs) for optimal TLR-ligand based adjuvant activity. The role of MyD88 signaling in B cell and DC in vaccine adjuvant has been previously investigated. In this study, we now demonstrate that the immune response was also reduced in mice with macrophage specific MyD88 deletion (Mac-MyD88-/-). We demonstrate that TLR-dependent adjuvants are potent inducers of germinal center (GCs) responses, but GCs are nearly absent in Mac-MyD88-/- mice following immunization with TLR-dependent adjuvants PorB or CpG, but not with TLR-independent adjuvants MF59 or Alum. Our findings, reveal a unique and here-to-for unrecognized importance of intact MyD88 signaling in macrophages, to allow for a robust vaccine induced immune responses when TLR-ligand based adjuvants are used.